2020
DOI: 10.1016/j.asmr.2020.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Superior Capsular Reconstruction: Fascia Lata Versus Acellular Dermal Allograft: A Systematic Review

Abstract: We systematically reviewed the literature to compare the clinical and radiologic outcomes and retear rates of superior capsular reconstruction (SCR) using fascia lata autograft (FLA) versus human dermal allograft (HDA) in cases of massive irreparable rotator cuff tears. Methods: Searches of Pub Med and Cochrane Library identified clinical studies addressing SCR using FLA and HDA. Two reviewers independently screened the titles, abstracts and full texts to extract data from eligible studies. Reported outcome me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…SCR with the use of the LHBT autograft yielded similar results with the traditional SCR in the direct comparison performed by Kocaoglu et al, including the retear rates (3/14 for the LHBT SCR versus 2/12 for SCR with a fascia lata) [26]. SCR graft retear rates have been reported in the literature and they range from 3.4-55% for human dermal allograft and 4.5-29% for fascia lata autografts, revealing less satisfactory results in the long-term [6,31]. Mihata et al reported that the success of the SCR depends mainly on graft healing [31].…”
Section: Interpretation Of the Results In The Context Of The Literaturesupporting
confidence: 54%
See 1 more Smart Citation
“…SCR with the use of the LHBT autograft yielded similar results with the traditional SCR in the direct comparison performed by Kocaoglu et al, including the retear rates (3/14 for the LHBT SCR versus 2/12 for SCR with a fascia lata) [26]. SCR graft retear rates have been reported in the literature and they range from 3.4-55% for human dermal allograft and 4.5-29% for fascia lata autografts, revealing less satisfactory results in the long-term [6,31]. Mihata et al reported that the success of the SCR depends mainly on graft healing [31].…”
Section: Interpretation Of the Results In The Context Of The Literaturesupporting
confidence: 54%
“…This static graft acts as a restraint against the superior migration of the humeral head, thus preventing the progression of RC tear arthropathy and yielding promising functional outcomes [ 1 ]. Several authors proposed the use of acellular dermal allograft to avoid the possible autograft donor site morbidity of the original technique, although biological healing between bone and dermal allografts is not yet fully investigated [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, fascia lata and human dermal graft could be used in SCR (23)(24)(25)(26). However, concerns about cost, donor site morbidity in case of autograft, increased surgical time and the significantly elongation of dermal graft during test need to be considered (27). Furthermore, an unstable shoulder works with an altered biomechanics and will undergo arthritic degeneration (15,16,19).…”
Section: Discussionmentioning
confidence: 99%
“…All patient reported outcomes improved between the pre-operative and 24-month postoperative assessments in both groups (SCR vs BG). The mean ASES, WORC and DASH scores at 24 months post-operatively were 77.9 +/-19.9 (95%CI 69.2 -86.4), 69.5 +/-24.5 (95%CI 58.9 -80.1) and 25…”
Section: Clinical Outcomesmentioning
confidence: 97%